Cuentos y cantos folclóricos como estrategias para el aprendizaje de la lengua kichwa en estudiantes de EGB” - Sinaluisa Auquilla, Rosa María (2024)
Through this research work, the project "Folklore stories and songs as strategies for learning the Kichwa language in 9th EGB students" of the "Adolfo Kolping" Educational Unit is fulfilled, where it was proposed to evaluate the effectiveness of folklore stories and songs as a learning strategy and the strengthening of this language, through a quantitative and qualitative (mixed) approach and the pre-experimental design with a sample of 19 students, from 9th General Basic Education. This study investigated teaching strategies based on the story "Yaya Chimpurasupa piñanakuy" by narrator Baltasar Remache and the song "Saraku-Maíz" by Manuela Bejarano, among others, which were used to encourage interest in learning the Kichwa language. In addition, a pre-test and a post-test were applied to determine the level of mastery of the Kichwa language. An illustrated corpus was also created as a teaching technique to promote learning of the Kichwa language. Finally, the results show that folk singing is one of the appropriate strategies to capture students' attention, stimulate their pronunciation and imagination, and promote meaningful learning. To the extent appropriate, this research determines folk tales and songs as one of the appropriate strategies that should be implemented in a classroom by teachers with the intention of better teaching-learning and strengthening of the Kichwa language in students since these strategies, from a pedagogical perspective promote development in areas such as; intellectual, social and language, promoting the mother tongue of Kichwa speakers, since it is essential to prioritize its strengthening to safeguard the linguistic legacy of the Kichwa communities.